Monitoring the Adoption of SPI-Related Best Practices. An Experience Report - Walter, Bartosz; Marović, Branko; Garnizov, Ivan; Wolski, Marcin; Todosijevic, Andrijana (Communications in Computer and Information Science, 2021)
Software Process Improvement requires significant effort related not only to the identification of relevant issues and providing adequate response to them, but also to the implementation and adoption of the changes. Best practices provide recommendations to software teams on how to address the identified objectives in practice, based on aggregated experience and knowledge. In the paper, we present the GÉANT experience and observations from the process of adopting the best practices, and present the setting we have been using.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Best practices; Software maturity evaluation; Software process improvement; SPI monitoring